Removal of phosphate and fluoride from industrial wastewater â A short review - Zulfiqar, M. (Trans Tech Publications Ltd, 2014)
Industries producing fertilizers, aluminium, steel, bricks, glass, and semiconductor discharge several thousand tons of phosphate and fluoride per year into the open atmosphere in the form of wastewater which cause many environmental issues as well as loss of drinking water. The objective of this review is to select the suitable method for the removal of phosphate and fluoride from industrial wastewater which is highly hazardous and acidic in nature. So that treated water can be reused for agricultural and industrial purposes. Industries discharge several thousand tons of phosphate and fluoride per year in the form of wastewater which cause many environmental issues and loss of drinking water. This review is provided with aimed a precise and accurate knowledge for the removal of phosphate and fluoride from industrial wastewater. A lot of technologies are available for the treatment of industrial wastewater treatment including chemical precipitation, crystallization, ion exchange, adsorption, reverse osmosis and nanofiltration methods. The selection of most suitable treatment technology is based on retention time, principle of operation, applications, chemicals and maintenance cost. Â© 2014 Trans Tech Publications, Switzerland.